SiP System-in-Package design and simulation mentor EE flow advanced design guide - Li, Suny 1974- (Publishing House of Electronics Industry/Wiley, 2017)
An advanced reference documenting, in detail, every step of a real System-in-Package (SiP) design flow Written by an engineer at the leading edge of SiP design and implementation, this book demonstrates how to design SiPs using Mentor EE Flow. Key topics covered include wire bonding, die stacks, cavity, flip chip and RDL (redistribution layer), Embedded Passive, RF design, concurrent design, Xtreme design, 3D real-time DRC (design rule checking), and SiP manufacture. Extensively illustrated throughout, System in Package Design and Simulation covers an array of issues of vital concern for SiP design and fabrication electronics engineers, as well as SiP users, including: -Cavity and sacked dies design -FlipChip and RDL design -Routing and coppering -3D Real-Time DRC check -SiP simulation technology -Mentor SiP Design and Simulation Platform Designed to function equally well as a reference, tutorial, and self-study, System in Package Design and Simulation is an indispensable working resource for every SiP designer, especially those who use Mentor design tools